Automated online exam proctoring system using computer vision and hybrid ML classi er - Hossain, Zarin Tahia; Roy, Protyasha; Nasir, Rina; Nawsheen, Sumaiya (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.